How sounds influence user safety decisions in a virtual construction simulator. (July 2016) - Lu, Xueqing; Davis, Steven
Highlights: Background sound in a high fidelity virtual environment enhances people's presence. More people make safe decisions in the virtual environment with background sounds. Salient sound is helpful in recognizing the related risks. Safe behaviors learnt in the virtual environment show in a corresponding physical environment. Abstract: The construction industry is well known as generating a high level of noise. Research has been done on the harm that construction noise has on people's health. However, apart from health issues, the effect that construction sounds have on safety issues such as workers' safety decisions is unknown. In this study, a virtual construction simulator has been employed to investigate the effect sound has on people's safety decisions. It is found that the addition of background sound to a high fidelity virtual reality simulator enhances people's sense of presence by creating a high level of normality. More people make safe decisions when background sound is present in the virtual construction simulator, and salient sound is helpful in recognizing the related risks. Safe behaviors learnt in a virtual construction environment can effectively reduce unsafe behaviors in a corresponding physical environment.